Productive Waqf Management Model - Nuradi; Husnul Khatimah; Irfan Syauqi Beik (Waraqat: Jurnal Ilmu-Ilmu Keislaman)
Productive waqf has emerged as a promising financial instrument for socio-economic development in Muslim-majority countries. However, existing studies are fragmented and lack a comprehensive synthesis of models and practices. This study aims to bridge this gap by conducting a Systematic Literature Review (SLR) on productive waqf management models published between 2019 and 2024. Using the PRISMA protocol, 51 eligible articles were selected from Scopus, Google Scholar, and SciSpace via Publish or Perish (PoP), and analyzed through VOSviewer for bibliometric mapping. The findings reveal that while productive waqf practices in Indonesia are evolving beyond the traditional 3M (Mosques, Madrasahs, and Tombs) model, they remain predominantly focused on cash-based waqf and business units. The utilization of waqf land for productive purposes is still significantly underexplored. Keyword mapping indicates emerging research trends around digitalization, governance, and nazir professionalism. This study contributes a synthesized framework of productive waqf models and highlights the need for standardization, certification of nazir, and innovation in land-based waqf development. The implications offer strategic insights for waqf stakeholders to align Islamic philanthropy with the Sustainable Development Goals (SDGs).